Economic Determinants of Capital Flight in Jordan: An Empirical Study - Al-basheer, Ameen B.; Al-Fawwaz, Torki M.; Alawneh, Ateyah M. (European Scientific Journal, ESJ, 2016)
The aim of this study is to estimate the constraints of Capital Flight during the period from 2000 to 2013. The statistical analysis showed a positive statistical significant relationship between the external public debt, taxes, economic openness, previous capital flight, and Capital flight in Jordan. However, it also showed a negative statistical significant relationship between the growth rate of the economy and capital flight. This was together with the most important recommendations of the need to monitor the flight of capital through creating a Department in the central bank to control money flight. Therefore, this was aimed in reducing the external public debts that increase the phenomenon of Capital flight and cooperate with international institutions and the United Nations to locate the place of money flight.